2015
DOI: 10.1155/2015/803971
|View full text |Cite
|
Sign up to set email alerts
|

An Organ System Approach to Explore the Antioxidative, Anti-Inflammatory, and Cytoprotective Actions of Resveratrol

Abstract: Resveratrol is a phenolic phytochemical, with a stilbene backbone, derived from edible plants such as grape and peanut. It is a bioactive molecule with physiological effects on multiple organ systems. Its effects range from the neuroprotective to the nephroprotective, including cardiovascular, neuronal, and antineoplastic responses as a part of its broad spectrum of action. In this review, we examine the effects of resveratrol on the following organ systems: the central nervous system, including neurological p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(71 citation statements)
references
References 98 publications
0
70
0
1
Order By: Relevance
“…RSV, a natural polyphenol, has potentially beneficial properties including reducing oxidative stress and decreasing inflammatory responses [9, 33, 34]. To the best of our knowledge, our study is the first to show the involvement of the Nrf2/TLR4 signaling pathway in RSV-mediated protection against renal IRI using in vivo and in vitro models.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…RSV, a natural polyphenol, has potentially beneficial properties including reducing oxidative stress and decreasing inflammatory responses [9, 33, 34]. To the best of our knowledge, our study is the first to show the involvement of the Nrf2/TLR4 signaling pathway in RSV-mediated protection against renal IRI using in vivo and in vitro models.…”
Section: Discussionmentioning
confidence: 83%
“…Resveratrol (RSV) is a stilbene polyphenolic compound found in grapes, berries, red wines, and peanut skins, and has been studied in many models such as coronary heart disease and diabetes due to its functions in reducing oxidative stress and inflammation [4-6]. In addition, many studies have shown that RSV can have protective effects on organs including the brain [7], heart [8], and kidney in animal IRI models because it reduces oxidative stress and exerts anti-inflammatory and anti-apoptotic effects [9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol was also reported to have immunomodulatory effects on lesional macrophages by counteracting inflammation in human M1 and M2 macrophages upon challenge with certain types of cholesterol [55] . In addition, resveratrol supplementation at 3 mg·kg -1 ·d -1 in a hypercholesterolemic rabbit model led to a reduction of atherosclerotic plaque size and density as well as a decrease in the initial layer thickness, which demonstrated that resveratrol had a potential therapeutic effect on AS [56,57] . However, researchers have noted that resveratrol does not add to the antiatherogenic effect of atorvastatin when these drugs are used together [58] .…”
Section: Pharmacological Intervention Of Autophagy In the Treatment Omentioning
confidence: 99%
“…It has been shown to have a multitude of effects including being anti-inflammatory, antioxidative, and cytoprotective. Known targets in the heart include increasing endothelial nitric oxide availability via the estrogen receptor-␣ and sirtuin-1, having direct and indirect antioxidant properties and reducing the production of reactive oxygen species, inhibiting NF-B and proinflammatory cytokines including TNF-␣, and enhancing insulin sensitivity via AMPK (61,65). Resveratrol has been shown to have a wide range of health benefits, so it was not surprising that in C-26 tumor-bearing mice, resveratrol reduced NF-B activity, improved heart mass, and attenuated the LV wall thinning and chamber dilation (100).…”
Section: Current Treatment Of Cardiac Atrophy In Cancer Cachexiamentioning
confidence: 99%